ARLTS1 variants and melanoma risk - Frank, Bernd; Meyer, Peter; Boettger, Melanie Barbara; Hemminki, Kari; Stapelmann, Henrike; Gast, Andreas; Schmitt, Christina; Kumar, Rajiv; Sergi, Consolato; Burwinkel, Barbara (INTERNATIONAL JOURNAL OF CANCER, 2006)
Variants in the tumor suppressor gene ARLTS1 (ADP‐ribosylation factor‐like tumor‐suppressor gene 1) have been shown to influence familial cancer risk. Both Cys148Arg and Trp149Stop were associated with an increased risk of familial or high‐risk familial breast cancer, respectively. We studied the impact of these gene variants on melanoma risk, investigating 351 melanoma patients and 804 control subjects. While ARLTS1 Trp149Stop did not influence melanoma risk (OR = 0.83, 95% CI = 0.37–1.88, p = 0.65), Cys148Arg revealed a statistically significant association with an increased risk for heterozygous carriers (OR = 1.43, 95% CI = 1.05–1.95, p = 0.02). An additional risk enhancement, though statistically non‐significant, was observed in individuals with multiple melanomas (OR = 2.33, 95% CI = 0.87–6.26, p = 0.08). © 2006 Wiley‐Liss, Inc.